Service Quality Affects BPJS Patient Satisfaction at the Pematang Health Center, Serang Regency, Banten in 2024 - Kurniyanti, Novia; Effendy, Ismail; Anggraini, Indah (PROMOTOR, 2024)
Health service providers must strive to improve the quality of services for the realization of the highest degree of public health. The purpose of this study is to find out and analyze the quality of service affecting BPJS patient satisfaction at the Pematang Health Center, Serang Regency, Banten in 2024. The research design uses an analytical survey with a cross sectional design. The population in this study is all patients who are treated using BPJS as many as 4,210 people with an accidental sampling technique with a sample of 98 people. The data analysis used used was univariate analysis, bivariate using chi-square and multivariate using logistic regression. The results of the logistic regression analysis that affected were the variables of immediate service p = 0.003, politeness p = 0.005 and effective communication p = 0.000 and the most influential variable was effective communication with an Exp B value of 13.922. The conclusion of the variables that do not affect is the use of information technology, physical facilities, quick response, skills and attitudes and the variables that affect are prompt service, politeness and effective communication and the most influential is effective communication. It is recommended to the Puskesmas to make a budget  for Communication Skills  training for all health workers, mentoring, and implementation by making the motto of the Pematang Health Center to be (smile, greeting, polite fast and precise). Providing services in a timely, polite, friendly manner and can maintain patient privacy in order to increase patient satisfaction and provide physical facilities such as (chairs, air conditioners, loudspeakers and machines to take no queue) as well as provide information on the use of mobile JKN.